2013
DOI: 10.1136/bmjopen-2013-003605
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of leaders in the implementation of Lean in a teaching hospital—barriers and facilitators in clinical practices: a qualitative study

Abstract: ObjectivesTo date, experiences of leaders in the implementation of Lean after a Lean Training Programme have not been systematically investigated within teaching hospitals. Existing studies have identified barriers and facilitators only from an improvement programme perspective and have not considered the experiences of leaders themselves. This study aims to bridge this gap.DesignSemistructured, indepth interviews.SettingOne of largest teaching hospitals in the Netherlands.Participants31 medical, surgical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 33 publications
2
82
0
5
Order By: Relevance
“…In the cases studied, the barriers faced were primarily associated with human factors, including employee distrust, medical interests, conflicts of interest, the frustration of previous attempts, adverse reactions due to lean healthcare's origins in the manufacturing sector and leadership with little training or involvement; other barriers included the lack of knowledge about new lean concepts and technological barriers such as employee computer use. These results corroborate the results found in several papers, such as Aij et al (), Bhat and Jnanesh (), Bhat et al () and Bhat and Jnanesh (), among others.…”
Section: Case Descriptionssupporting
confidence: 93%
“…In the cases studied, the barriers faced were primarily associated with human factors, including employee distrust, medical interests, conflicts of interest, the frustration of previous attempts, adverse reactions due to lean healthcare's origins in the manufacturing sector and leadership with little training or involvement; other barriers included the lack of knowledge about new lean concepts and technological barriers such as employee computer use. These results corroborate the results found in several papers, such as Aij et al (), Bhat and Jnanesh (), Bhat et al () and Bhat and Jnanesh (), among others.…”
Section: Case Descriptionssupporting
confidence: 93%
“…Reports of previous single-intervention studies have not found the need for extra support for clinical teams, 4,[16][17][18] suggesting that this may indeed be a consequence of the complication added by combined interventions, and participants' recognition of the need for extra support. Our more general findings on the challenge posed by the surgical context reflect those of other authors, who have highlighted how lack of senior support 14,19 and the complexity of clinical microsystems that are interdependent but not always well co-ordinated [19][20][21][22] can stymie improvement efforts. This indicates a need for care in the application of the S3 approach elsewhere, particularly outside formal research contexts where resources for support may be fewer, and where the expertise, legitimacy and neutral brokerage offered by an external team may not be available.…”
Section: Discussionsupporting
confidence: 55%
“…However, the existence of high labour productivity might not directly benefit a specific department in terms of higher budgets in the specific hospital context of our study. Budget constraints have urged health-care organisations to improve efficiency and reduce costs while maintaining quality (Aij et al, 2013). As a result, cost-containment strategies are highly relevant in the health-care industry and include tight budgets and a focus on keeping down labour costs (Schut and Van de Ven, 2005).…”
Section: Introductionmentioning
confidence: 99%